1988
DOI: 10.1164/ajrccm/138.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Quartz But Not Iron Oxide Causes Air-Flow Obstruction, Emphysema, and Small Airways Lesions in the Rat

Abstract: Recent epidemiologic studies have suggested that some workers exposed to inorganic dusts develop air-flow obstruction independent of or greater than that produced by cigarette smoke; the morphologic basis of this effect is unknown. To investigate this problem, we administered saline alone, 10 mg iron oxide (an inert dust), or 10 or 30 mg of quartz to rats by intratracheal instillation. Animals were killed after 30 days, and pulmonary function and morphologic changes were examined. The iron oxide group was simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 3 publications
1
17
0
1
Order By: Relevance
“…Experimental evidence from rats also indicates that exposure to crystalline silica causes emphysema and abnormally thick walls in the small airways with associated functional changes of airflow obstruction in rats (5,6).…”
mentioning
confidence: 98%
“…Experimental evidence from rats also indicates that exposure to crystalline silica causes emphysema and abnormally thick walls in the small airways with associated functional changes of airflow obstruction in rats (5,6).…”
mentioning
confidence: 98%
“…Again, there is overlap between the lesions caused by dust and those caused by cigarette smoke in the airways, but careful morphometric studies make it clear that the dust lesions are distinct from the cigarette lesions [4, 51 and that they appear to be associated with some degree of airflow obstruction. In a previously reported experiment, we found that silica (quartz) administered to rats by intratracheal instillation produced not only silicotic nodules, but also functional and morphologic evidence of emphysema and smallairway changes [6]. In that study we measured only two morphologic parameters: the thickness of the walls of small airways, and mean linear intercept, a very general parameter of airspace size.…”
Section: Discussionmentioning
confidence: 94%
“…The fact that mineral dusts might also be associated with elastic fiber destruction has not been previously demonstrated. However, if, as we have previously suggested [6], mineral dusts produce emphysema by evoking a long-standing inflammatory response, then elastic fiber destruction is not surprising, and the process is in many ways analogous to the chronic inflammatory response thought to be crucial to the development of cigarette smoke-induced emphysema in humans [14-161. The major difference is the greatly compressed time scale seen in the mineral dust-treated animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dependendo da dose e do tempo de avaliação após a instilação desta substância elastolítica, consegue-se reproduzir enfisema em porções diferentes dos pulmões, podendo-se obter destruição do parênquima pulmonar mais próxima aos brônquios, enfisema centroacinar, que se aproxima mais ao enfisema que ocorre em seres humanos ocasionado pelo tabagismo, ou um enfisema em porções mais distais dos pulmões, de distribuição panacinar, mais semelhante ao observado em pessoas que apresentam deficiência em α1-antitripsina (138,139,140,141 A presença do material particulado na câmara sem filtros foi fundamental para o aumento do estresse oxidativo, levando a uma piora do enfisema e indução de remodelamento nos animais que receberam papaína.…”
Section: Análise Estatísticaunclassified